Low-volume walking HIIT: Efficient strategy to improve physical capacity and reduce the risk of cardiovascular disease in older women with type 2 diabetes. Issue 5 (September 2021) - Marcotte-Chénard, A.; Tremblay, D.; Mony, M.-M.; Brochu, M.; Dionne, I.J.; Langlois, M.F.; Mampuya, W.; Morais, J.; Tessier, D.; Riesco, E.
Abstract: Background and aims: To compare the effect of a low-volume walking high-intensity interval training (HIIT) to moderate-intensity continuous training (MICT) on risk of cardiovascular diseases and physical capacity in older women with type 2 diabetes (T2D). Methods: Thirty inactive older women with T2D were randomized into either HIIT (75 min/week) or MICT (150 min/week). Cardiovascular risk profile (lipid profile; waist circumference and fat mass; resting, post-exercise and ambulatory blood pressure [BP]; VO2 peak; UKPDS score; ABC's) and physical capacity were assessed before and after a 12-week intervention. Results: While resting systolic and diastolic BP (all p ≤ 0.01) were reduced, ambulatory BP ( p ≥ 0.49) and lipid profile ( p ≥ 0.40) remained unchanged after the intervention. Although VO2 peak increased to a similar extent in both groups ( p = 0.015), the distance covered during the 6MWT ( p = 0.01) and grip strength ( p = 0.02) increased to a greater extend in HIIT. The UKPDS risk score decreased in both groups after the intervention ( p = 0.03) and 31% of the participants reached the ABC's compared to 24% at baseline. Conclusion: Low-volume walking HIIT is an efficient exercise intervention for older women with T2D as it improved some CVD risk factors and physical capacity. Nevertheless, neither low-volume HIIT nor MICT is sufficient to affect ambulatory blood pressure in T2D patients. Highlights: With half the exercise workload, low-volume HIIT generates benefits on cardiovascular risk profile similalry to MICT. Low-volume HIIT provides greater benefits on physical capacity compared to MICT after a 12-week exercise intervention. Both low-volume HIIT and MICT improved VO2 peak, regardless of the training workload.